Stable isotope records (d18O and d13C) of speleothems from Amazonian lowlands over the last 3000 years - Della Libera, Marcela Eduarda; Novello, Valdir Felipe; Cauhy, Julio; Cruz, Francisco William (PANGAEA, 2022)
The stable isotope records are based on two stalagmites, PIM4 and PIM5, collected in Cuíca cave (11°40°S, 60°38°W, ~310 m a.s.l.) located in Pimenta Bueno city, Rondônia State, SW Amazon region in Brazil. The d18O record was interpreted as a proxy for the activity of the South American Monsoon System (SAMS), and the d13C record as a proxy for vegetation changes and local hydrology, as discussed in the paper Paleoclimatic and paleoenvironmental changes in Amazonian lowlands over the last three millennia (Della Libera et al., 2022). The d18O and d13C analyses were performed at the Stable Isotope Laboratory at the Institute of Geoscience of the University of São Paulo (Brazil) using a Thermo-Finnigan Delta Plus Advantage mass spectrometer. The notation d in the results refers to the relative Vienna Pee Dee Belemnite (VPDB) standard with the per mil deviation, with uncertainties on the values of 0.1‰ for both analyses. 706 samples of powdered carbonate were extracted from PIM4 for d18O and d13C analyses using a computer-operated MicroMill Micro-Sampling Device with a 0.1 mm diameter drill bit. Sampling occurred along the central growth axis of the speleothem, with the first 20 mm from the top sampled with a 0.1 mm spacing, while from 20 mm to the bottom, a spacing of 0.2 mm was applied. For PIM5, 805 samples were obtained using a manual Sherline Mill with a 0.1 diameter drill bit, with a constant spacing of 0.4 mm along the central growth axis of the speleothem. The geochronology of both PIM4 and PIM5 was established by means of the U/Th dating method, using an inductively coupled plasma-mass spectrometry (ICP-MS) technique at the Geochronology Laboratory at the University of Minnesota (USA) and at the Institute of Global Environmental Change, Xi'an Jiaotong University (China). The sampling for the U/Th dating was performed by extracting ~100 mg of powdered carbonate with a dentist drill along each stalagmite growth axis, with 21 U/Th ages for PIM4 and 16 for PIM5, yielding an overall 2-yrs resolution for the isotope records. The Cuíca cave d18O record composite is a merge of PIM4 and PIM5 d18O records through normalization (i.e., by subtracting the mean and dividing by the standard deviation) of the data inside the overlapping period, averaging both series and then reconstructing the shorter time series with the mean and standard deviation of the longer one, for each interpolated isotope time series (Monte-Carlo simulation).
Keywords: Amazon forest; d13C; d18O; Holocene climate; Oxygen and carbon stable isotopes; Paleoclimate; paleoenvironment; South American Monsoon System; speleothem; Stable isotope; stalagmite; Vegetation dynamics